Kumonest papasan chair / Muhammad Azfar Danial Mohd Nazri - Mohd Nazri, Muhammad Azfar Danial (Universiti Teknologi MARA, Kedah, 2025)
KUMONEST: Nature's Papasan Chair Spider Web in Your Living Room" This final portfolio project examines furniture design with a surprising but fascinating subject: Spider Web. KumoNest's curved, rounded curves cradle and support the body, giving a cocoon-like reclining sensation inspired by a spider's web. This chair combines modern style with classic comfort, made of eco-friendly, durable materials. The open, airy construction and deep, soft cushions allow you to burrow into it, making it perfect for unwinding after a long day or for when you just want to feel comfortable. KumoNest is inspired by the natural world and adds a touch of organic elegance to any area. The web-like structure is complimented by a variety of materials and finishes that combine elegance and durability. KumoNest converts any location into a calm hideaway, allowing one to withdraw from the outer world and reconnect with oneself, whether on a balcony, while reading a book, or in a garden. KumoNest is more than a chair; it's a haven of comfort, connection, and peaceful retreat for those who value design, leisure, and nature.